Spicy food consumption and biological aging across multiple organ systems: a longitudinal analysis from the China Multi-Ethnic cohort - Ning Zhang; Feng Hong; Yi Xiang; Yuan Zhang; Wen Qian; Xuehui Zhang; Liling Chen; Zhuoma Duoji; Xiong Xiao; Xing Zhao (Nutrition Journal)
Abstract Background Biological aging is a common starting point for many chronic diseases and multimorbidity. Spicy food consumption is showing a growing trend worldwide. However, the association of spicy food consumption with the comprehensive biological age (BA) and organ-specific BAs remains unclear. Methods This study included 7874 participants from the China Multi-Ethnic Cohort (CMEC), all participating in baseline and follow-up surveys. The CMEC was located in Southwest China, which has become one of the most prominent and typical regions regarding spicy food consumption in China and the world. We constructed comprehensive BA and organ-specific BAs based on composite indicators using the widely validated Klemera-Doubal method. The frequency of intake of spicy food was obtained by an electronic questionnaire. Follow-up analyses adjusted for baseline data were then employed to assess the longitudinal associations of spicy food consumption at baseline with both the comprehensive BA and the organ-specific BAs at follow-up. Results Compared with non-spicy consumers, spicy consumers showed a decrease in comprehensive BA acceleration, with adjusted β = −0.23 (− 0.60 to 0.13) for 1–2 days/week, β = −0.69 (− 1.10 to − 0.29) for 3–5 days/week and − 0.32 (− 0.63 to − 0.01) years for 6–7 days/week, respectively. Higher estimates were observed for metabolic and kidney BA accelerations than for cardiopulmonary and liver BA accelerations. Compared to non-spicy consumers, spicy consumers showed a decrease in metabolic BA acceleration (3–5 days/week: β = −0.76 (− 1.28 to − 0.24) years) and kidney BA acceleration (3–5 days/week: β = −1.89 (− 2.76 to − 1.02) years). Conclusion Spicy foods may have potential benefits for biological aging. Our findings highlight that spicy foods may slow comprehensive and organ-specific biological aging, especially metabolic and kidney biological aging. Graphical abstract